Comparative analyses of complete plastid genomes of representative species of subfamily Convallarioideae (Asparagaceae) - Chen, Xingru; Wu, Shaode; Nie, Zelong; Wen, Jun; Meng, Ying (Phytotaxa, 2024)
Convallarioideae are a subfamily of Asparagaceae, a morphologically diverse group comprising seven tribes, i.e., Eriospermeae, Rusceae, Dracaeneae, Nolineae, Convallarieae, Ophiopogoneae and Polygonateae, and two genera unclassified to tribe. In this study, we conducted comparative plastid genome (plastome) analyses of seven species representing seven clades of the subfamily. The results showed that all plastomes exhibited standard conserved quadripartite structures with inverted repeats (26,261–26,522 bp) separated by a large single-copy region (83,007–85,692 bp) and a small single-copy region (18,205–18,707 bp). Each plastome has 137 genes, including 87 protein-coding genes, 38 transfer RNAs and 8 ribosomal RNA genes. Furthermore, we detected 33–61 simple sequence repeats in six categories and 39–57 long repeats in four categories. We selected eleven hotspots as primer sites for potential molecular markers. Phylogenetic analysis of the subfamily revealed that all the tribes are strongly supported except for Polygonateae, but weak support was observed among the main clades in the subfamily.